PERANCANGAN SISTEM INFORMASI KOHORT IBU HAMIL MENGGUNAKAN MICROSOFT VISUAL STUDIO 2010 - Latifah, Annisa; Utami, Nuraeni (JURSIMA (Jurnal Sistem Informasi dan Manajemen), 2021)
The target data for the 2020 MCH program at the Ahmad Yani Health Center in Bandung City are 472 pregnant women. Every pregnant woman is obliged to check her pregnancy 4 times in 9 months, in which documentation of the development of pregnant women needs to be reported in order to support the health of mothers and children. The recording and reporting system for the cohort registration of pregnant women at the Ahmad Yani Health Center in Bandung City is still manual, so that data incompleteness often occurs due to the many components that must be filled manually in the cohort register, which results in delays in submitting reports to the Head of the Puskesmas and the Bandung City Health Office. This study aims to design a cohort information system for pregnant women at the Ahmad Yani Health Center in Bandung City which can facilitate midwives in recording, processing and reporting data quickly and accurately. The development method used is Waterfall with DFD modeling (Data Flow Diagram) which is implemented using Microsoft Visual Studio 2010 and programming language Microsoft Access 2016 as the database. Data collection techniques used are observation, interviews and literature study. With this information system, it is hoped that it will facilitate data collection on patients, data on routine visits for pregnant women, data collection on midwives, and presentation of reports periodically, by region, visits, detection of risk factors, referrals and computerized quarterly visit charts.